Human Hair Keratin Direct Electrochemistry and In Situ Interaction with p-Toluenediamine and p-Aminophenol Hair Dye Precursors using a Keratin Electrochemical Biosensor - Souza, João C. [UNESP]; Machini, Wesley B. S.; Zanoni, Maria Valnice B. [UNESP]; Oliveira-Brett, Ana Maria (Wiley, 2020)
Keratin is the main protein in hair strands. The process of dyeing hair with permanent dyes is quite complex and involves oxidative reactions between precursors, such as p-toluenediamine (PTD) and p-aminophenol (PAP), and coupler agents, in alkaline and oxidative medium, inside the hair. The electrochemical behaviour of native and denatured human hair keratin, assessed by using a keratin multilayer film adsorbed on glassy carbon electrode, and its interaction with hair dye precursors, PTD and PAP, by using electrochemical techniques, was investigated. Native and denatured keratin electrochemical oxidation showed two oxidation peaks; the first was first attributed to the cysteine amino acid residues, and the second to the cysteine and methionine amino acids residues. The PTD- and PAP-keratin-hair dye interactions induced damage, causing the unfolding of the keratin morphological structure, and new additional peaks of the cysteine and tyrosine amino acid residues were revealed.
Keywords: electrochemical oxidation; hair dyes; keratin; p-aminophenol; p-toluenediamine